Combustion synthesis of metal oxides nano particles: An efficient route to produce nano materials for diverse applications. (2022) - Ramesha, S.; Jyotsna Aithal, Shubhra; Sureshkumar, K.; Ramakrishnappa, T.; Praveen, B.M.; Pruthviraj, R.D.
Abstract: Different nanoscale tungsten oxides with phenomenal photocatalytic properties were orchestrated through a super-fast arrangement ignition amalgamation strategy . The outcomes showed that the WO3 and W18 O49 could be orchestrated with various fills (glycine, urea, urea and citrus extract) and the powders introduced mesoporous structures with various morphologies, for example, nanoparticles, nanorods and nanoneedles. Itemized response components of different frameworks were distinguished, and the particular jobs of various powers were examined . Also, the integrated powders showed fantastic photocatalytic proficiency, debasing natural mixtures in 50 min under UV-obvious light illumination. The work recommends that arrangement ignition combination can be utilized as another procedure to plan nanosized stoichiometric and oxygen-opportunity rich nonstoichiometric oxides with brilliant properties .